Quality Unknown : The Invisible Water Crisis - Damania, Richard; Desbureaux, Sébastien; Rodella, Aude-Sophie; Russ, Jason; Zaveri, Esha (Washington, DC: World Bank, 2019)
Water quantity—too much in the case of floods, or too little in the case of droughts—grabs public attention and the media spotlight. Water quality—being predominantly invisible and hard to detect—goes largely unnoticed. Quality Unknown: The Invisible Water Crisis presents new evidence and new data that call urgent attention to the hidden dangers lying beneath water’s surface. It shows how poor water quality stalls economic progress, stymies human potential, and reduces food production.